The Signaling Network Controlling C. elegans Vulval Cell Fate Patterning - Shin, Hanna (J Dev Biol, 2018)
EGF, emitted by the Anchor Cell, patterns six equipotent C. elegans vulval precursor cells to assume a precise array of three cell fates with high fidelity. A group of core and modulatory signaling cascades forms a signaling network that demonstrates plasticity during the transition from naïve to terminally differentiated cells. In this review, we summarize the history of classical developmental manipulations and molecular genetics experiments that led to our understanding of the signals governing this process, and discuss principles of signal transduction and developmental biology that have emerged from these studies.